The Post-Pandemic World and the Foreign Policy Imperatives - Oshewolo, Roseline; Oshewolo, Segun; Oniemola, Roseline F. (ABUAD Journal of Social and Management Sciences, 2024)
Considering the destructive and disruptive potential of pathogens, this research identifies new lessons and policy imperatives in the governance of future scenarios of pandemics. Although foreign policy players and other critical stakeholders are beginning to recognise the values of global health in foreign policy thinking and decision-making, there are still major gaps in pandemic response, particularly as the COVID-19 pandemic has revealed. To plug the observed gaps, this paper calls attention to three political / foreign policy priorities. First, critical actors must enhance their preparedness for future pandemics by building massive health infrastructure, supersizing the health corps, and investing in programmes that will aid their capacity to predict a health emergency before it occurs. Second, foreign policy professionals must prioritize humanity over high politics in global pandemic response. Third, foreign policy actors must place adequate focus on migration health going into the future.